Association of remimazolam with delirium and cognitive function in elderly patients undergoing general anesthesia or procedural sedation: a meta-analysis of randomized controlled trials - Wang, Yao; Gou, Zi-han; Wang, Gan-min; Ye, Lun-hui; Chen, Li; Wang, Qian (Frontiers in Medicine, 2025)
BackgroundRemimazolam is an ultra-short-acting benzodiazepine with sedative effects, but its impact on postoperative delirium (POD) and cognitive function in elderly patients remains unclear. This study aimed to compare the incidence of POD and cognitive function between remimazolam and other sedatives in elderly patients undergoing general anesthesia or procedural sedation.MethodsThis study included randomized controlled trials (RCTs) comparing remimazolam with other sedatives in elderly patients undergoing general anesthesia or procedural sedation. A comprehensive search was conducted in Ovid MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, and the China National Knowledge Infrastructure (CNKI) from inception to January 2, 2025, without language restrictions. Data were pooled quantitatively using a random-effects model. The primary outcomes were the incidence of POD and cognitive function.ResultsA total of 1,808 elderly patients from 11 RCTs were included. Compared with other sedatives, remimazolam did not increase the incidence of POD (OR: 0.62, 95% CI [0.23, 1.68], p = 0.35, I2 = 73%), but improve cognitive function, as measured by Mini-Mental State Examination scores, the seventh postoperative day (MD: 0.53, 95% CI [0.16, 0.91], p = 0.005, I2 = 28). Additionally, remimazolam significantly reduced the incidence of hypotension (OR: 0.27, 95% CI [0.21, 0.35], p < 0.001, I2 = 0%) and respiratory depression (OR: 0.35, 95% CI [0.17, 0.69], p = 0.003, I2 = 0%) compared to other sedatives. However, no significant differences were observed between remimazolam and other sedatives for postoperative nausea and vomiting (OR: 1.31, 95% CI [0.91, 1.89], p = 0.15, I2 = 0%) or hypoxemia (OR: 0.69, 95% CI [0.35, 1.34], p = 0.28, I2 = 0%).ConclusionOverall, the use of remimazolam in the elderly population appears to pose fewer risks than other sedatives. It does not increase the incidence of postoperative delirium following general anesthesia or sedation, but it improves postoperative cognitive function and provides more stable hemodynamics. However, further well-designed RCTs with long-term follow-up are needed to establish a standardized medication regimen and optimal dosage tailored to elderly patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, registration number (CRD4202563620).